Literasi Digital dan Integrasi Teknologi TPACK pada Buku Teks Bahasa Indonesia Kelas XI - Anggun Fatma Mustika; Maulinda Nurul; Umi Nur Sholikhah; Elen Inderasari (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2026)
ABSTRACT This study aims to examine the form of digital literacy and technology integration in Indonesian language textbooks grade XI in the Merdeka Curriculum. The study using a qualitative descriptive approach, using the book